Stepping Stones Triple P: The theoretical basis and development of an evidence-based positive parenting program for families with a child who has a disability - Sanders, M.; Mazzucchelli, Trevor; Studman, L. (Informa Healthcare, 2004)
Stepping Stones Triple P is the first in a series of programs based on the successful Triple P-Positive Parenting Program that has been specifically designed for families who have a child with a disability. This paper presents the rationale, theoretical foundations, historical development and distinguishing features of the program. The multi-level intervention adopts a self regulation framework in consulting with parents that involves the promotion of parental self sufficiency, self efficacy, self management skills, personal agency and problem solving skills. It describes the key program design features, intervention techniques, model of clinical consultation, its clinical applicability, and empirical base. We describe a 10 session individually administered version of the program, known as Standard Stepping Stones. We also discuss the important role of training, supervision and agency support in disseminating the program.